The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1111/1471-0307.12065
|View full text |Cite
|
Sign up to set email alerts
|

Influence of carboxymethylcellulose on the physicochemical, rheological and sensory attributes of a low‐fat Domiati cheese

Abstract: The physicochemical, rheological and sensory attributes of a low-fat Domiati cheese produced using carboxymethylcellulose (CMC), a hydrocolloid, at 0.4, 0.6, 0.8 and 1% (w⁄w) were examined during the ripening period. Results indicated that, as the carboxymethylcellulose content of cheese milk increased, cheese yield and moisture of low-fat Domiati cheese significantly increased but the protein, salt and fat values significantly decreased. Rheological parameters were significantly lower in cheeses made with CMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Adding CMC to the formulation affected the moisture content. In the study conducted by Abd Elhamid (2013), the effects of using 0.4%, 0.6%, 0.8% and 1.0% carboxymethyl cellulose (CMC) on the physicochemical, rheological and sensory properties of low‐fat Domiati cheese during ripening were examined. According to the results obtained, it was reported that as the CMC ratio increased, moisture content increased, but protein, salt and fat values decreased significantly.…”
Section: Resultsmentioning
confidence: 99%
“…Adding CMC to the formulation affected the moisture content. In the study conducted by Abd Elhamid (2013), the effects of using 0.4%, 0.6%, 0.8% and 1.0% carboxymethyl cellulose (CMC) on the physicochemical, rheological and sensory properties of low‐fat Domiati cheese during ripening were examined. According to the results obtained, it was reported that as the CMC ratio increased, moisture content increased, but protein, salt and fat values decreased significantly.…”
Section: Resultsmentioning
confidence: 99%
“…), and is known as an important source of protein, calcium and phosphorus in human nutrition. As a result of the amount and type of fat cheese contains, it has been linked to colon cancer, coronary artery disease and health related problems (Abd Elhamid ). Due to low level of fat found in Aho cheese (6–9%), its popularity has increased recently among people having high cholesterol or other similar health problem.…”
Section: Introductionmentioning
confidence: 99%